BE_STEUERREKURS 100 2020 122 vom 16. Oktober 2018 - BE Steuerrekursgericht (2018)
Grundstückgewinnsteuer/ Interkant. Doppelbesteuerung/ gewerbsmässiger Liegenschaftshändler/ Händlerpauschale | die Grundstückgewinnsteuer